2021
DOI: 10.4236/ojas.2021.113034
|View full text |Cite
|
Sign up to set email alerts
|

Age and Calcium Sources in Laying Hen Feed Affect Calcium Digestibility

Abstract: The apparent calcium (Ca) digestibility coefficient (ADC) and true digestibility coefficient (TDC) of different inorganic calcium sources were determined in laying hens of different ages. Three Ca digestibility tests were carried out, each assessing 240 Lohmann Brown lineage laying hens distributed in a completely randomized design. Nine dietary treatments were arranged in a 3 × 3 factorial design consisting of three ages (40, 50 and 70 weeks) × three Ca (dicalcium phosphate (DCP) sources, fine (FL) and coarse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Older hens often produce larger, weak-shelled eggs ( Al-Batshan et al, 1994 ) and exhibit compromised skeletal structure. Efficiency of intestinal calcium absorption decreases with age ( Diana et al, 2021 ), leading to increased reliance on bone-derived calcium contributing to fractures ( Gregory and Wilkins, 1989 ). Elucidating physiological mechanisms responsible for the uptake and utilization of calcium and phosphorus throughout the hen’s productive lifecycle will provide insights that can be used to develop strategies limiting economic losses to producers and improving animal welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Older hens often produce larger, weak-shelled eggs ( Al-Batshan et al, 1994 ) and exhibit compromised skeletal structure. Efficiency of intestinal calcium absorption decreases with age ( Diana et al, 2021 ), leading to increased reliance on bone-derived calcium contributing to fractures ( Gregory and Wilkins, 1989 ). Elucidating physiological mechanisms responsible for the uptake and utilization of calcium and phosphorus throughout the hen’s productive lifecycle will provide insights that can be used to develop strategies limiting economic losses to producers and improving animal welfare.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, limestone is the main ingredient used as a Ca source in diets of laying hens. However, Ca digestibility can vary according to limestone particle sizes (limestone with fine vs. coarse grains) (Diana et al, 2021). Studies show that fine-grained limestone has a higher in vitro solubility than coarsergrained limestone and that as in vitro solubility increases, in vivo solubility decreases (Cheng and Coon, 1990a;Zhang and Coon, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, limestone is the main ingredient used as a source of Ca in the diets of laying hens. However, Ca digestibility can vary according to limestone granulometries (limestone with fine granulometry vs coarse grain) (Diana et al, 2021). Studies have shown that fine-grained limestone has a higher in vitro solubility than coarser-grained limestone and that the higher the in vitro solubility, the lower the in vivo solubility Zhang and Coon, 1997).…”
Section: Introductionmentioning
confidence: 99%